2017
DOI: 10.1242/dev.143370
|View full text |Cite
|
Sign up to set email alerts
|

Soluble APP functions as a vascular niche signal that controls adult neural stem cell number

Abstract: The molecular mechanism by which NSC number is controlled in the neurogenic regions of the adult brain is not fully understood but it has been shown that vascular niche signals regulate neural stem cell (NSC) quiescence and growth. Here, we have uncovered a role for soluble amyloid precursor protein (sAPP) as a vascular niche signal in the subventricular zone (SVZ) of the lateral ventricle of the adult mouse brain. sAPP suppresses NSC growth in culture. Further in vivo studies on the role of APP in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Nevertheless, deciphering the complex mechanisms involved in this process may be very challenging in the brain. In a recent article in Development , Sato and colleagues revealed an important component of the neural stem cell (NSC) niche: an endothelial cell-derived molecule that keeps NSCs’ quiescence in the subventricular zone in vivo (Sato et al, 2017). The authors identified by in vitro assays soluble amyloid precursor protein (APP) as an extrinsic cue that suppresses NSCs’ growth, and enhances neurosphereforming ability, while retaining their multipotency.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, deciphering the complex mechanisms involved in this process may be very challenging in the brain. In a recent article in Development , Sato and colleagues revealed an important component of the neural stem cell (NSC) niche: an endothelial cell-derived molecule that keeps NSCs’ quiescence in the subventricular zone in vivo (Sato et al, 2017). The authors identified by in vitro assays soluble amyloid precursor protein (APP) as an extrinsic cue that suppresses NSCs’ growth, and enhances neurosphereforming ability, while retaining their multipotency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sato and colleagues investigated the role of APPs on NSCs in vivo by using APP-null mouse model. The authors discovered that, in the absence of APP, NSCs’ proliferation in the subventricular zone increases, suggesting that APP is important for NSCs’ quiescence in their niche (Sato et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations